Anwar Shah (ed.). Public Expenditure Analysis. Washington, D. C.: The World Bank, 2005. xxxi+256 pages. Paperback. Price not given. (The Pakistan Development Review, 2005)
Public Expenditure Analysis is the 7th edition in the “Public Sector Governance and Accountability Series” edited by Anwar Shah. The book attempts to contribute to public sector reforms by improving governance in the public expenditure analysis—to disburse the benefits to grossroots levels in the developing countries. It deals with the intricate issue of equity in both the tax burdens and public spending and evaluates performance of government in safeguarding the interests of the poor and other disadvantaged groups of the society, such as women, children, and minorities. The eight chapters of the book that consist of papers prepared by distinguished authors systematically develop a framework for a right-based approach to citizen empowerment by creating an institutional design with appropriate rules, restraints, and incentives to make the public sector responsive and accountable to the average voter.